2023
DOI: 10.3390/life13081689
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers and Their Diagnostic Significance in Ovarian Cancer

Abstract: Ovarian cancer (OC) is characterized by silent progression and late-stage diagnosis. It is critical to detect and accurately diagnose the disease early to improve survival rates. Tumor markers have emerged as valuable tools in the diagnosis and management of OC, offering non-invasive and cost-effective options for screening, monitoring, and prognosis. Purpose: This paper explores the diagnostic importance of various tumor markers including CA-125, CA15-3, CA 19-9, HE4,hCG, inhibin, AFP, and LDH, and their impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…In an informational study by Yokoi et al, the demarcation of early-stage ovarian cancers from benign excrescences was achieved with an emotional perceptivity of 86 and a particularity of 83 by employing a panel of eight miRNAs. Similarly, the presence of miRNAs was detected in EVs insulated from dressed ovarian cancer cell lines [6].…”
Section: Micrornasmentioning
confidence: 86%
See 2 more Smart Citations
“…In an informational study by Yokoi et al, the demarcation of early-stage ovarian cancers from benign excrescences was achieved with an emotional perceptivity of 86 and a particularity of 83 by employing a panel of eight miRNAs. Similarly, the presence of miRNAs was detected in EVs insulated from dressed ovarian cancer cell lines [6].…”
Section: Micrornasmentioning
confidence: 86%
“…Globally, OC Is recognized as the most lethal gynecological cancer and ranks fifth in cancer-related deaths among women in the Western world. such as biomarker testers, could improve the chances of early detection [6].…”
Section: Significance Of Early Diagnosis In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Kozak KR et al [44] concluded that combining CA125, TTR, Hb, ApoAI, and TF is expected to significantly improve early ovarian cancer detection. According to Matsas et al [45] the use of a combination of CA-125, CA15-3, CA 19-9, HE4, and hCG (human chorionic gonadotropin) has the potential to improve early detection of the disease and can make a valuable contribution to diagnosing, monitoring, and prognosticating ovarian cancer [45]. Yurkovetsky Z et al [46] created a set of biomarkers consisting of CA-125, HE4, CEA, and VCAM-1 (VCAM-1-vascular cell adhesion molecule-1).…”
Section: Ca125 and Its Use In Combination With Other Markersmentioning
confidence: 99%
“…The reproductive factors include early onset of menstruation, late menopause and never having been pregnant. The treatment options for ovarian cancer have surgery, radiation therapy and chemotherapy ( Konstantinopoulos and Matulonis, 2023 ; Matsas et al, 2023 ). Because drug resistance is one important cause of therapeutic failure, it is pivotal to explore the drug resistant mechanisms and to overcome drug resistance in ovarian cancer ( Pawlowska et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%